PENGARUH PESAN IKLAN TOTAL ALMEERA VERSI “DETERJEN HALAL PERTAMA DI INDONESIA” PADA MEDIA TELEVISI TERHADAP SIKAP KONSUMEN (STUDI PADA WANITA MUSLIM DI BANDUNG) - Vanita Maya Sri Hutami; Martha Tri Lestari (Dialektika, 2018)
In recent years, many halal products have emerged in Indonesia.. The use of halal predicate is a new strategy in marketing various products. The market share of a very large Islamic religion is clearly appealing. Total Almeera is one of the trademarks of PT. Total Chemindo Loka is innovating by issuing the first halal detergent in Indonesia. One of the marketing strategies that has been used by Total Almeera is issuing ads on television using emotional appeal. Detergent ads generally highlight the advantages of its products that can clean and soften and the fragrance of clothing, then Total Almeera presented with a different ad style by carrying the concept of hijrah. In this study involves one independent variable namely Advertising Message (X) and one dependent variable Consumer Attitude (Y). The results showed that the influence of Ad Message variable (X) to Consumer Attitude variable (Y) was 54%. While the remaining 46% influenced by other factors not examined in this study. The t-test results show that the Ad Message variable (X) has a tcount greater than the ttable value because tcount (21,594)> ttable (1.96) of significance level 0,000 <0.05 then H0 is rejected and H1 is accepted. This means that Total Almeera’s advertising message as "Deterjen Halal Pertama di Indonesia" on television towards consumer attitude.